2014
DOI: 10.1155/2014/701565
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Digital Serious Games for the Assessment, Rehabilitation, and Prediction of Dementia

Abstract: Dementia is a serious, progressive, and often debilitating illness with no known cure, having a severe adverse effect on memory, behaviour, reasoning, and communication. A comprehensive review of current refereed research material in the use of games in this area is scarce and suffers from being orientated towards commercially available games or derivatives such as “Dr. Kawashima’s brain training.” There is much lesser concern for bespoke research grade alternatives. This review will attempt to assess the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Recent studies could show that applications such as tablet mobile devices with integrated memory training apps can be used even by people with early stage of dementia [ 1 , 2 ]. Some reviews reported that exergames that combine physical activity with digital gaming have also been found wide application in healthy [ 3 ], disabled older adults [ 4 ], and in people with cognitive impairment or dementia [ 5 - 7 ]. Just to name a few examples, a computerized Tai Chi game using the Microsoft’s motion-capture device Kinect [ 8 ] or a computer tele-rehabilitation platform that combines game-based exercises with telemonitoring [ 9 ] has the potential to improve motor and cognitive functions in the older population.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies could show that applications such as tablet mobile devices with integrated memory training apps can be used even by people with early stage of dementia [ 1 , 2 ]. Some reviews reported that exergames that combine physical activity with digital gaming have also been found wide application in healthy [ 3 ], disabled older adults [ 4 ], and in people with cognitive impairment or dementia [ 5 - 7 ]. Just to name a few examples, a computerized Tai Chi game using the Microsoft’s motion-capture device Kinect [ 8 ] or a computer tele-rehabilitation platform that combines game-based exercises with telemonitoring [ 9 ] has the potential to improve motor and cognitive functions in the older population.…”
Section: Introductionmentioning
confidence: 99%
“…The use of game technology and 3D game engine techniques for interactive visualisation is becoming increasingly popular in eHealth and health data analysis. Such works, for example, are an interactive environment for supporting the assessment, rehabilitation and prediction of dementia [36] and virtual reality for assessing cognition in the elderly [37].…”
Section: Utilising Gaming Platform For Interactive Visualisationmentioning
confidence: 99%
“…Showing positive results in multiple domains, such as prevention [15], rehabilitation [14], neurocognitive stimulation [16], assessment [17] and monitoring neurocognitive changes [18], leading to beneficial changes, when it comes to brain plasticity [19], changing the brain's structure [20] and facilitating the impact of neurocognitive stimulation on everyday functioning [6]. However, the use of serious games, with older people, is still in an early phase [21] and there is little information when it comes to the impact of these programs on the users' quotidian activities and on their quality life [22].…”
Section: State Of the Artmentioning
confidence: 99%